Cyst-like lesions of the knee joint and their relation to incident knee pain and development of radiographic osteoarthritis: The MOST study - Guermazi, Ali (2010)
OBJECTIVE: To determine whether intra- and periarticular cyst-like lesions of the knee are associated with incident knee pain and incident radiographic knee osteoarthritis (OA). DESIGN: The Multicenter Osteoarthritis (MOST) Study is a cohort of individuals who have or are at high risk for knee OA. Using a nested case-control study design, we investigated the associations of cyst-like lesions (Baker’s, meniscal and proximal tibiofibular joint (PTFJ) cysts, and prepatellar and anserine bursitides) with (a) incident pain at 15- or 30-month follow-up and (b) incident radiographic OA at 30-month follow-up. Baseline cyst-like lesions were scored semiquantitatively using the Whole Organ Magnetic Resonance Imaging Score (WORMS). Conditional logistic regression models were used to assess the relation between these lesions and the outcomes, adjusting for potential confounding factors (i.e. cartilage loss, meniscal damage, bone marrow lesions, synovitis and joint effusion, which were also scored using WORMS). RESULTS: Incident knee pain study included 157 cases and 336 controls. Prevalence of meniscal and PTFJ cysts in the case group was twice that in the control group (9 (6%) vs. 9 (3%) and 9 (6%) vs. 10 (3%), respectively). Incident radiographic OA study included 149 cases and 298 controls. Prevalence of grade 2 Baker’s cysts and PTFJ cysts in the case group was approximately 4 times that in the control group (16 [11%] vs. 9 [3%] and 6 [4%] vs. 3 [1%], respectively). However, none of the cyst-like lesions was associated with incident pain or radiographic OA after fully adjusted logistic regression analyses and correction of p-values for multiple comparisons. CONCLUSION: None of the analyzed lesions was an independent predictor of incident knee pain or radiographic OA. Intra- and periarticular cyst-like lesions are likely to be a secondary phenomenon seen in painful or OA-affected knees, rather than a primary trigger for incident knee pain or radiographic OA.